Analysing Skills of Planning, Conduct, and Assessment In Teachers During Online Mathematics Teaching - Rikana Sulistyaningrum; Sutama Sutama; Anatri Desstya (Profesi Pendidikan Dasar, 2021)
The field of education has been confronted with a difficult situation as a result of the COVID-19 pandemic, which has infected hundreds of countries around the world. The government has placed multiple policies to combat the effects of the pandemic, including stopping all face-to-face teaching and replacing them with online learning. This sudden shift has demanded educators to be professional and be skillfully adaptive in their work processes. This issue is over three months during the pandemic, specifically from September to November 2020, whereby six teachers were analyzed. In conclusion, this study found that some teachers were able to utilize online media, while some still struggled with it during the COVID-19 pandemic.